A study of the determinants of smoking behaviour and the association of smoking with lung function of male secondary school students in Kota Bharu. - Musa, Razlan
Smoking in Malaysia has mostly been a male activity and it is among men that there has been a high prevalence of smoking prevalence. This is true for adult as well as for adolescents, based on the National Health and Morbidity Surveys (NHMS) and several studies conducted in Malaysia (Country Report: Malaysia, 2001 ). The high overall smoking prevalence in Malaysia has been actually contributed by the prevalence among male population. In the National Health and Morbidity Survey 1996, the smoking prevalence of Malaysian population aged 18 years and above was 24.8 percent. The prevalence among men was 49.2 percent compared to 3.5 percent among women. This was higher than the previous National Health and Morbidity survey conducted in 1986 that found a total smoking prevalence of 21.5 percent, with male smoking rates at 41 percent compared to 4 percent among women (Country Report: Malaysia, 2001 ). The prevalence can be considered high in both surveys even though they are not comparable due to the differences in population characteristics.